2018
DOI: 10.1109/tnnls.2018.2791458
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Artificial Neural Networks Using a Digital Memristor Simulator

Abstract: This paper presents a fully digital implementation of a memristor hardware (HW) simulator, as the core of an emulator, based on a behavioral model of voltage-controlled threshold-type bipolar memristors. Compared to other analog solutions, the proposed digital design is compact, easily reconfigurable, demonstrates very good matching with the mathematical model on which it is based, and complies with all the required features for memristor emulators. We validated its functionality using Altera Quartus II and Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In contrast, the memristor emulators are easy to obtain and cost efficient. The reported memristor emulators can be divided into two types: analog emulators are on basis of off‐the‐shelf electronic components 29–33 ; digital emulators mainly rely on a microcontroller 34,35 . In 2019, we designed an analog emulator for the threshold‐type binary memristor, where the threshold sensitive behavior is implemented by the diodes 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the memristor emulators are easy to obtain and cost efficient. The reported memristor emulators can be divided into two types: analog emulators are on basis of off‐the‐shelf electronic components 29–33 ; digital emulators mainly rely on a microcontroller 34,35 . In 2019, we designed an analog emulator for the threshold‐type binary memristor, where the threshold sensitive behavior is implemented by the diodes 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Memristor possesses the significant advantage of resistance-tunable features for behaving like a synapse and is universally considered to be the emerging building blocks of brain-like ANNs (Wang et al, 2016;Li C. et al, 2018;Liu et al, 2018;Yan et al, 2018Yan et al, , 2019aYoon et al, 2018;Zhao et al, 2020). Some progress has been made in emulating synapse behavior and constructing hardware ANNs with memristors devices (Wang et al, 2012;Kim et al, 2015;Zhang et al, 2017;Hu et al, 2018;Ntinas et al, 2018). Prezioso et al (2015) experimentally demonstrated an artificial neural network using metal-oxide based memristors integrated into a dense, transistor-free crossbar circuit.…”
Section: Introductionmentioning
confidence: 99%
“…However, the memristor device is still an immature technology and faces some challenges at the device and architectural levels which delays its availability as a commercial component. On the other hand, several emulator circuits have been reported in the literature to imitate the behavior of real memristor devices [19]. Field-Programmable Gate Array (FPGA) plat- [3] ∼ 80 [8] <2 [7] Switching speed (ns) 20 [3] 250 [8] 5 [7] FIGURE 1: Typical CNN architecture with the four main layers: Convolution, Pooling, ReLU and fully connected [9].…”
Section: Introductionmentioning
confidence: 99%